Study of Some Biochemical and Blood Parameters as Screening Markers for Breast Cancer Patients before Adjuvant Therapy in Thi Qar Government-Southern Iraq - Jamal Harbi Hussein Alsaadi (Journal of Global Pharma Technology, 2019)
Breast cancer is the most common malignancy disease in women. The study includes Eighty-three cases were divided according age into women (patients and healthy ) average age more than forty five( Age > 45 year) Fifty - five confirmed subject of breast cancer patients (n = 42), healthy as control group (n=18) and women (patients and healthy) average age less than forty five Age (< 45 year) twenty three distributed to(2) groups too .The first group confirmed (n=13)cases of breast cancer patients and second group (n=10)as control group. They were evaluated for blood parameters and some biochemical parameters that are associated with breast cancer occurring in Thi-Qar Government .Iraq. study has revealed that significant decreasing (p<0.001) observed in HB , PCV, RBC and WBC levels and a significant increasing (P < 0.05) Platelets , ESR and Monocyte retrospectively in cancer patients comparison to normal control subjects and significant correlation (P< 0.05) between Neutrophil and Lymphocyte , rates of NLR and PLR were significantly higher in breast cancer patients compared to control group at Age > 45 year .While the results showed for women mean Age (< 45 year). The mean haemoglobin (Hb) , packed cell volume( PCV) and Red blood cells (RBC) levels in the patient group were a significantly and lower than the control group at (p>0.05). There was high significant differences in WBCs neutrophils, lymphocytes, monocytes also significant difference ESR (p>0.01) compared with healthy female .The values of NLR and PLR were showed significantly but no high in the patients compare with healthy group. In this study biochemical Parameters(lipid profile ) ,were showed a significant decreasing at (p>0.01) for ;lipid profile parameters (Cholesterol, T.G, HDL and LDL) compared with biochemical Parameters measurement values of female control mean Age > 45 year , while results showed that significant increasing at (p>0.05)in some lipid profiles in breast cancer patients compared with healthy control group in women Age (<45 year).Keywords: Breast cancer, Lipid profile, Blood Parameters.